Pengaruh Persepsi Kegunaan dan Atribut Produk terhadap Keputusan Pembelian Smartphone Berteknologi Android di Yogyakarta - Yohannes Vemberi (Sekolah Tinggi Ilmu Ekonomi SBI, 2015)
This reserch examines the behavior of consumers in the decision to buy a smartphone based on android whether they are affected usefulness and product attributes. Reserchers distributing questionnaires in the Yogyakarta area with respondents android-based smarphone users. this study used 75 samples. the analysis used is multile regression analysis using independent variables usefulness, quality, price, design, and features while the dependet variable was the decision to buy. the study concluded that usefulness influence on purchase decisions tech android smartphone, quality attributes do not affect the decision to buy a smartphone tech android. the price attributes influence the decision to buy a smartphone tech android. design attributes influence the decision to buy a smartphone tech android. feature attribut influence the decision to buy a smartphone tech android. usefulness, quality, price, design and featres together influence the decision to uy a smartphone tech android.